Optimising expression of the recombinant fusion protein biopesticide ω-hexatoxin-Hv1a/GNA in Pichia pastoris: sequence modifications and a simple method for the generation of multi-copy strains. (1st August 2014) - Pyati, Prashant; Fitches, Elaine; Gatehouse, John A
Abstract: Production of recombinant protein bio-insecticides on a commercial scale can only be cost effective if host strains with very high expression levels are available. A recombinant fusion protein containing an arthropod toxin, ω-hexatoxin-Hv1a, (from funnel web spider Hadronyche versuta ) linked to snowdrop lectin ( Galanthus nivalis agglutinin; GNA) is an effective oral insecticide and candidate biopesticide. However, the fusion protein was vulnerable to proteolysis during production in the yeast Pichia pastoris . To prevent proteolysis, the Hv1a/GNA fusion expression construct was modified by site-directed mutagenesis to remove a potential Kex2 cleavage site at the C-terminus of the Hv1a peptide. To obtain a high expressing clone of P. pastoris to produce recombinant Hv1a/GNA, a straightforward method was used to produce multi-copy expression plasmids, which does not require multiple integrations to give clones of P. pastoris containing high copy numbers of the introduced gene. Removal of the Kex2 site resulted in increased levels of intact fusion protein expressed in wild-type P. pastoris strains, improving levels of intact recombinant protein recoverable. Incorporation of a C-terminal (His)6 tag enabled single step purification of the fusion protein. These modifications did not affect the insecticidal activity of the recombinant toxin towards lepidopteran larvae. Introduction of multiple expression cassettes increased the amount of secreted recombinant fusion protein in a laboratory scale fermentation by almost tenfold on a per litre of culture basis. Simple modifications in the expression construct can be advantageous for the generation of high expressing P. pastoris strains for production of a recombinant protein, without altering its functional properties.